Approach to shoulder instability: a randomized, controlled trial - Julien Caron, MD FRCSC; Kellen Walsh, MD FRCSC; Tinghua Zhang, MSc; Rashed AlAhmed, MBChB MSc FRCSC; Peter B. MacDonald, MD FRCSC; Cristina Bassi, MD; J Whitcomb Pollock, MD FRCSC MSc; Katie McIlquham, BSc; Peter Lapner, MD FRCSC (JSES International, 2025)
Background: The significant rate of recurrent instability following arthroscopic stabilization surgery points to a need for an evidence-based treatment approach. The instability severity index Score (ISI score) is a point-based algorithm that may be used to assist clinicians in selecting the optimal treatment approach, but its efficacy compared with a traditional treatment algorithm has not been previously validated. The aim was to compare two surgical treatment algorithms: the ISI score and a conventional treatment algorithm (CTA). Methods: This was a prospective, randomized controlled trial involving participants who were randomized to either the ISI score or CTA and were followed for 24 months postrandomization. In the ISI score cohort, patients underwent a Latarjet procedure if they presented with a score >3 points. Those scoring ISI score ≦3 points underwent an arthroscopic Bankart repair. Patients randomized to the CTA group underwent a Latarjet procedure if the glenoid bone loss was > 25%. The primary outcome was the Western Ontario Shoulder Instability Index. Secondary outcomes included the American Shoulder and Elbow Surgeons score as well as recurrence rates between groups. Results: Sixty-three patients were randomized to ISI score (n = 31) or CTA (n = 32). At two years, the Western Ontario Shoulder Instability Index score was similar between groups (ISI score: 84.1 ± 16.9, CTA: 85.7 ± 12.5, P = .70). Similarly, no differences were detected in American Shoulder and Elbow Surgeons scores (ISI score: 93.2 ± 16.2, CTA: 92.6 ± 9.9, P = .89). Apprehension was reported in 18.5% for the ISI score group and 20% in the CTA group (P = 1.00). At a 24-month follow-up, there was no difference in redislocations: one in ISI score group and none in the CTA group (P = .48). There were two revision surgeries in the ISI score group and two in the CTA group. Conclusion: This study did not demonstrate any differences in functional outcomes, the incidence of apprehension, or failure rates between the two treatment algorithms at 24-month follow-up.